Financial Effects of Transformation to IFRSs in Saudi Markets - Ali Mohamed, Abdel Rahman Musa (Journal of Economics and Administrative Sciences, 2020)
The study objective is measure the financial effects of the transition from Saudi accounting standards to international accounting standards and the reasons for those effects, The study followed two methodological approaches the first was descriptive approach by reviewing the studies and reports and opinions of experts on the differences between the two types of standards and the possible effects of transition and monitoring and summarize scientifically; The second method is the statistical tests to identify the differences between the two types of standards, The study data were collected from the financial statements before and after the transition of a sample of the Saudi financial market companies which are most affected by the transformation their number (41), The study find that the transition to IFRS has had a Significantly effect on the reduce of the return on assets; basic earnings per share; equity; total comprehensive income, and Increase in the value of current liabilities. financial effects of the transition may be return mainly to reclassification and some differences that required re-measurement of financial statement items.